COMMONALITIES AND VARIATIONS IN THE SEMANTIC AND STRUCTURAL USE OF FLORA IN ENGLISH AND UZBEK DESCRIPTIONS - Ibrohimova Nasiba Mirzohid qizi (TADQIQOTLAR, 2025)
ANNOTATION This article analyzes the semantic and structural usage of flora-related terms in English and Uzbek. It highlights the similarities and differences in expressing human characteristics, emotions, and values through plant imagery. The comparative study also explores metaphorical usage and grammatical structures in both languages.